THE USE OF ALTERNATIVE TECHNIQUES USED IN SURGERY WITHOUT BLOOD AND HEMODERIVATED TRANSFUSION: A LITERATURE REVIEW (CIPEEX, 2022)
ALTHOUGH BLOOD TRANSFUSION IS WIDELY USED, ESPECIALLY IN CASES OF POSTOPERATIVE ANEMIA AND EXCESSIVE BLEEDING, EVIDENCE-BASED MEDICINE ASSOCIATES THIS TECHNIQUE WITH INCREASING RISKS OF MORBIDITY AND MORTALITY. THE PURPOSE OF THIS STUDY IS TO DESCRIBE AND ANALYZE THE EFFICACY OF THESE TECHNIQUES USED IN SURGERY WITHOUT BLOOD TRANSFUSION, OF BLOOD PRODUCTS AND BLOOD COMPONENTS, FROM THE GUIDING QUESTION "WHAT IS THE EFFECTIVENESS OF SURGERY WITH ALTERNATIVE TECHNIQUES FOR THE USE OF BLOOD, BLOOD PRODUCTS AND BLOOD COMPONENTS?" THE RESEARCH WAS DONE ON THE MEDICAL PLATFORMS PUBMED (SCIENTIFIC ELECTRONIC LIBRARY ONLINE) AND THE LANCET, BEING SELECTED 22 ARTICLES PUBLISHED BETWEEN 2012 AND 2018, THAT EXPOSED ALTERNATIVE TECHNIQUES ACCOMPANIED BY TESTS AND EVALUATIONS WITH THE COMMON GOAL OF AVOIDING BLOOD TRANSFUSION. THUS, IT WAS EVIDENCED THAT THE USE OF SURGICAL AND CLINICAL ALTERNATIVES TO TRANSFUSION, SUCH AS ADMINISTRATION OF ERYTHROPOIETIN, INTRAOPERATIVE BLOOD RECOVERY, MINIMALLY INVASIVE SURGERIES, BLOOD PRESERVATION, ACUTE NORMOVOLEMIC HEMODILUTION, OXYGEN CARRIER SOLUTIONS, CARDIOPULMONARY BYPASS , NOREPINEPHRINE COMBINED WITH INTRAOPERATIVE RESTRICTIVE HYDRATION WITH RINGER'S MALEATE SOLUTION AND ADMINISTRATION OF COAGULATION FACTORS PROVED TO BE EFFECTIVE FOR BETTER TREATMENT OF PATIENTS IN THEIR PARTICULARITIES, RESULTING IN BETTER PROGNOSIS AND DROP IN MORBIDITY AND MORTALITY RATES AND REHOSPITALIZATION DUE TO POST- COMPARED TO THE CONSERVATIVE PROCEDURE (USE OF TRANSFUSION), WHICH ALLOWS THE SELECTION OF EFFICIENT TREATMENTS THAT RESPECT THE BELIEFS OF RELIGIOUS COMMUNITIES AGAINST RECEIVING BLOOD, MINIMIZE OPERATIONAL COSTS AND REDUCE EXPOSURE THE PATIENT AT RISK.
Keywords: Bloodless Medical and Surgical Procedures. Preservation of Blood. Blood transfusion. Surgery.